Mental disorder and psychic suffering: social representations of primary health care professionals (Research, Society and Development, 2021)
Primary Health Care is the preferred gateway to the Unified Health System and one of the attention points to the population’s mental health. The aim of this study was to understand the social representations of psychic suffering and mental disorders for professionals who work in reference teams of Basic Health Units with a Family Health Strategy and to identify them in the face of influences on decision-making regarding the elaboration of the therapeutic treatment plan. It is a qualitative, descriptive-exploratory research with a cross-sectional design, based on the theory of social representations developed by Serge Moscovici. Data were collected between April and June 2020, in a health district of a southern capital of the country, through semi-structured interviews and a socio-demographic questionnaire. 17 workers participated of the study, including doctors, nurses and nursing assistants / technicians. The results indicate that there is a paradigm shift in progress, although professionals find limitations both in training and in institutions to exercise comprehensive mental health care. It is concluded that the professionals of Primary Health Care differentiate the concepts of mental disorder and psychic suffering, however this does not significantly impact the decision-making about the therapeutic treatment plan, a fact that correlates to the current assistance structure, which demands on professional fast and resolutive interventions, which implies the preferential choice for drug therapy and referral to specialized services.